Precision Synthesis of Boron-Doped Graphene Nanoribbons: Recent Progress and Perspectives - Zhang, Jin-Jiang; Ma, Ji; Feng, Xinliang (Macromolecular Chemistry and Physics, 2023)
Structurally precision graphene nanoribbons (GNRs) have attracted great interest considering their prospective applications as organic carbon materials for nanoelectronics. The electronic properties of GNRs not only critically depend on the edge structure and width but also on the heteroatom type, doping position, and concentration. Motivated by the recent undisputable progress in the synthesis of stable boron-doped polycyclic aromatic hydrocarbons (B-PAHs), considerable efforts have been devoted to the precision synthesis of the corresponding boron-doped GNRs (B-GNRs) via bottom-up synthesis approach in recent years in view of the extraordinary ability of boron doping on modulating their physiochemical properties. In this review, an overview of the bottom-up organic synthesis of B-GNRs, including the precursor design and synthesis, structure characterization of the resulting B-GNRs, and investigation of their electronic properties is provided. Moreover, the future challenges and perspectives regarding the bottom-up synthesis of B-GNRs are also discussed. The authors hope that this review will further stimulate the synthesis and device integrations of B-GNRs with a combined effort from different disciplines.
CRIS-Team Scopus Importer:2023-03-20
Keywords: boron doping; bottom-up synthesis; electronic structures; graphene nanoribbons; polycyclic aromatic hydrocarbons